Transcriptional response of Aspergillus fumigatus to copper and the role of the Cu chaperones. Issue 1 (1st January 2021) - Anabosi, Duaa; Meir, Zohar; Shadkchan, Yana; Handelman, Mariana; Abou-Kandil, Ammar; Yap, Annie; Urlings, Daniel; Gold, Morgan S.; Krappmann, Sven; Haas, Hubertus; Osherov, Nir
ABSTRACT: Aspergillus fumigatus is the leading cause of life-threatening invasive mold infections in immunocompromised individuals. This ubiquitous saprophyte possesses several natural attributes allowing it to evade the immune system, including the ability to withstand high toxic Cu concentrations within the phagosomes of macrophages and neutrophils. We previously established that at high levels, Cu binds and activates the A. fumigatus transcription factor AceA, which upregulates the expression of the Cu exporter CrpA to expel excess Cu. Deletion of aceA or crpA result in extreme Cu sensitivity and attenuated virulence. To identify other elements participating in resistance to Cu, we performed a genome-wide analysis of the transcriptome by RNAseq to analyze the AceA-dependent response of A. fumigatus to excess Cu. We deleted key genes whose transcription was strongly upregulated by high Cu, including those encoding homologs of the three Cu chaperones cox17, atx1 and ccs1 . Detailed analysis of these genes indicates that in A. fumigatus, cox17 is an essential gene with a possible role in respiration, the atxA gene product participates in reductive iron uptake and ccsA encodes the Cu chaperone activating A. fumigatus Sod1. Interestingly, although the ccsA -null strain was extremely sensitive to high Cu and oxidative stress, it was not attenuated in virulence in a mouse model of invasive pulmonary aspergillosis. Our work provides (i) a detailed view of the genome-wide transcriptional response of A. fumigatus to excess Cu, (ii) identification of the AceA-dependent transcriptome and (iii) analysis of the roles of the three Cu chaperones cox17, atxA and ccsA.